Micro-Raman spectroscopy study of optically trapped erythrocytes in malaria, dengue and leptospirosis infections - Jacob, Sanu Susan; Lukose, Jijo; Bankapur, Aseefhali; Mithun, N.; Vani Lakshmi, R.; Acharya, Mahendra; Rao, Pragna; Kamath, Asha; Baby, Prathap M.; Rao, Raghavendra K.; Chidangil, Santhosh (Frontiers in Medicine, 2022)
Anemia is a severe and generic hematological derangement seen in malaria, dengue and leptospirosis, forming a significant cause of morbidity and mortality in the tropical belt. During the course of these infectious diseases, circulating red blood cells are imperiled to the direct ill-effects of the infectious pathogen in the body as well as to the pro-inflammatory cytokines generated as a consequence of the infection. This research aimed to explore the Raman spectra of live red cells that were extracted from patients infected with malaria, dengue, and leptospirosis. Red cells were optically trapped and micro-Raman probed using a 785nm Diode laser. RBCs from samples of all three diseases displayed Raman signatures that were significantly altered from the normal/healthy. Distinct spectral markers that were common across all the four groups were obtained from various standardized multivariate analytical methods. Following exhaustive examination of multiple studies, we propose these spectral wavenumbers as ‘Raman markers of eryptosis’. Findings in our study display that anemia-triggering infections can inflict variations in the healthy status of red cells, easily identifiable by selectively analyzing specific Raman markers. Additionally, this study also highlights relevant statistical tools that can be utilized to study Raman spectral data from biological samples which could help identify the very significant Raman peaks from the spectral band. This approach of RBC analysis can foster a better understanding of red cell behavior and their alterations exhibited in health and disease.